Microclimate variation and estimated heat stress of runners in the 2020 Tokyo Olympic Marathon - Kosaka, E.; Iida, A.; Vanos, J.; Middel, A.; Yokohari, M.; Brown, R. (Atmosphere, 2018)
The Tokyo 2020 Olympic Games will be held in July and August. As these are the hottest months in Tokyo, the risk of heat stress to athletes and spectators in outdoor sporting events is a serious concern. This study focuses on the marathon races, which are held outside for a prolonged time, and evaluates the potential heat stress of marathon runners using the COMFA (COMfort FormulA) Human Heat Balance (HBB) Model. The study applies a four-step procedure: (a) measure the thermal environment along the marathon course; (b) estimate heat stress on runners by applying COMFA; (c) identify locations where runners may be exposed to extreme heat stress; and (d) discuss measures to mitigate the heat stress on runners. On clear sunny days, the entire course is rated as `dangerous` or `extremely dangerous`, and within the latter half of the course, there is a 10-km portion where values continuously exceed the extremely dangerous level. Findings illustrate which stretches have the highest need for mitigation measures, such as starting the race one hour earlier, allowing runners to run in the shade of buildings or making use of urban greenery including expanding the tree canopy.